2021
DOI: 10.1007/s00402-021-03899-9
|View full text |Cite
|
Sign up to set email alerts
|

Polytetrafluoroethylene (PTFE) suture vs fiberwire and polypropylene in flexor tendon repair

Abstract: Background In this study, we evaluate the value of novel suture material based on monofilamentous-extruded polyfluoroethylene (PTFE) compared to polypropylene (PPL) and Fiberwire (FW). Materials and methods 60 flexor tendons were harvested from fresh cadaveric upper extremities. 4–0 sutures strands were used in the PPL, FW and PTFE group. Knotting properties and mechanical characteristics of the suture materials were evaluated. A 4-strand locked cruciate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…According to Naleway et al, most published reports on the tensile behavior of various sutures only focus on breaking force, and detailed reports comparing other important tensile properties, such as failure elongation, failure stress, failure strain, modulus, and full stress–strain curves across suture materials, are quite limited [ 9 ]. Most researchers agree that simple knotting alone influences materials that may differ significantly in their tensile strengths and elastic/plastic deformation characteristics, but can still display comparable elongations at failure [ 6 ]. Von Fraunhofer et al [ 10 ] described that all sutures in their study showed decreased tensile strength and elongation at failure when knotted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Naleway et al, most published reports on the tensile behavior of various sutures only focus on breaking force, and detailed reports comparing other important tensile properties, such as failure elongation, failure stress, failure strain, modulus, and full stress–strain curves across suture materials, are quite limited [ 9 ]. Most researchers agree that simple knotting alone influences materials that may differ significantly in their tensile strengths and elastic/plastic deformation characteristics, but can still display comparable elongations at failure [ 6 ]. Von Fraunhofer et al [ 10 ] described that all sutures in their study showed decreased tensile strength and elongation at failure when knotted.…”
Section: Discussionmentioning
confidence: 99%
“…For the measurement, a 100 N measuring component was mounted with a velocity setting of 300 mm/min. This method has been validated before [ 5 , 6 ]. The force required to evoke tear of the material was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we also plan to refine, optimize, and combine the developed S 2 sutures with our recently developed flexible surgical endoscopic robots for in-vivo experiments on a living animal. Our developed S 2 sutures will also be a potential candidate for other surgical applications such as abdominal wound closure, hernia repair, sternal closure, or orthopedic procedures [49][50][51][52] .…”
Section: Discussionmentioning
confidence: 99%